REKONSTRUKSI PENDIDIKAN PESANTREN (Studi Komparatif Pemikiran Abdurrahman Wahid dan Nurcholis Madjid) - Al Muiz Nasichin Mochamad (Universitas Islam Balitar, 2017)
Islamic Boarding School (pesantren) is an educational institution based on society where leadership is centered on Kyai. This study aimed to describe leadership management of pesantren by comparing insights from Abdurrahan Wajid and Nurcholis Madjid, two Islamic scholars whose great insights were predominant in the development of modern perspectives and education system in pesantren. This research used library research, exploring conceptual insights of revolutionary perspectives from Abdurrahman Wahid and Nurcholis Madjid about modernization and pesantren reconstruction. The study discovered that Abdurrahman Wahid and Nurcholis Madjid pioneered establishment of pesantren modernity foundation to implement “Al-Muhafadhatu -˜ala al-qadim al-ashalihwa al-akhdzu bi al-jadid al-ashlah– in its own characteristics. Reconstruction emphasized on purpose, curriculum and methods of education in pesantren as well as Islamic leadership.